Differential Roles for the Retinoblastoma Protein in Cycling and Quiescent Neural Populations - Andrusiak, Matthew (Université d'Ottawa / University of Ottawa, 2013)
While the genetics of retinoblastoma and the implications of the retinoblastoma susceptibility gene, RB1, are well described, there is still scarce evidence to suggest why RB1 acts in such a cell-type specific manner. Using the murine cortex as a model, we examined the effects of RB1 deletion of cycling neural progenitors and post-mitotic neurons, in order to ascertain cell-type specific functions in the central nervous system. Using the previously identified cell-cycle independent role for Rb in tangential migration, we validated Rb/E2f regulation of neogenin and implicated it in this process. In quiescent cortical neurons, we identified a pivotal role for Rb in neuronal survival. Unlike in cycling progenitors, in post-mitotic neurons Rb specifically represses the expression of cell-cycle associated genes in an E2f-dependent manner. Finally, in cortical neurons in the absence of Rb, we observe an activation of chromatin at E2f associated promoters. To determine the role of direct interaction between Rb and chromatin modifying enzymes, we utilized an acute LXCXE-binding deficient mutant paradigm. We report that the LXCXE binding motif is dispensable in establishment and maintenance of cortical neuron quiescence and survival. The activation state of E2f-responsive promoters appears to be dependent on E2f-activity and not simply Rb-mediated repression. Taken as a whole, this thesis serves to support the hypothesis that Rb plays a diverse role in different cell-types by regulation of unique gene targets and regulatory mechanisms. Characterizing specific cancer-initiating populations and understanding the specific function of Rb will help in the treatment of many cancers resulting from RB1 mutation or mutation within the Rb/E2f pathway.
Keywords: Brain Development; Cell Death; Cell Cycle; Rb/E2f Pathway